Tear Proteases and Protease Inhibitors: Potential Biomarkers and Disease Drivers in Ocular Surface Disease. (March 2020) - Fu, Runzhong; Klinngam, Wannita; Heur, Martin; Edman, Maria C.; Hamm-Alvarez, Sarah F.
Abstract : Abstract: Tears are highly concentrated in proteins relative to other biofluids, and a notable fraction of tear proteins are proteases and protease inhibitors. These components are present in a delicate equilibrium that maintains ocular surface homeostasis in response to physiological and temporal cues. Dysregulation of the activity of protease and protease inhibitors in tears occurs in ocular surface diseases including dry eye and infection, and ocular surface conditions including wound healing after refractive surgery and contact lens (CL) wear. Measurement of these changes can provide general information regarding ocular surface health and, increasingly, has the potential to give specific clues regarding disease diagnosis and guidance for treatment. Here, we review three major categories of tear proteases (matrix metalloproteinases, cathepsins, and plasminogen activators [PAs]) and their endogenous inhibitors (tissue inhibitors of metalloproteinases, cystatins, and PA inhibitors), and the changes in these factors associated with dry eye, infection and allergy, refractive surgery, and CLs. We highlight suggestions for development of these and other protease/protease inhibitor biomarkers in this promising field.